Study of emission of radioactive gaseous effluents in the production of 18F-FDG - Heber Simões Videira; Beatriz Luci Fernandes; Uysha de Souza Fonda; Maria Inês Calil Cury Guimarães; Marcelo Kaminski Lenzi; Emerson Nobuyuki Itikawa; Miriam Roseli Yoshie Okamoto; Daniel Henrique Uzueli; Rubens Abe; Ronielly de Lima Santos; Marcos Aurélio Vieira; ELIANE FERNANDA DIAS; et al. (Brazilian Journal of Radiation Sciences, 2019)
The number of units producing radiopharmaceuticals with a half-life of fewer than two hours has increased with the growth of PET technology in Brazil. In the production of such radiopharmaceuticals such as 18F-FDG or 11C-PIB, gaseous waste is formed. The International Atomic Energy Agency (IAEA) proposes a methodology that can be used to evaluate the dispersion of these gaseous effluents. This work has retrospectively evaluated the emission of radioactive gaseous effluents generated in the production of 18F-FDG, in order, to delimit yield values of radioactive waste in the gaseous form and to verify the effectiveness and the design of the safety elements of the exhaust system evaluated before the standards of the National Nuclear Energy Commission (CNEN) and IAEA recommendations. Thirty-six productions of 18F-FDG were found.